Sulfonated nano cellulose film with high proton conductivity and preparation method thereof

By conducting light-proof oxidation and Schiff base reduction amination reaction on cellulose, sulfonic acid groups are introduced to prepare a high-proton conductivity sulfonated nanocellulose film, which solves the problems of low proton conductivity and non-degradability of cellulose, and achieves efficient proton conductivity and environmentally friendly preparation process.

CN119708574AActive Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411994192.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing cellulose has low proton conductivity, is non-degradable, and the preparation process will indirectly pollute the environment, making it difficult to meet the requirements of proton conduction performance of proton exchange membrane fuel cells.

Method used

By oxidizing cellulose with light barrier oxidation reaction using sodium periodate in deionized water at pH 2 to 3, bisaldehyde cellulose is produced, and sulfonic acid groups are introduced through Schiff base reduction amination reaction to prepare a sulfonated nanocellulose film with high proton conductivity.

Benefits of technology

The proton conductivity of cellulose has been increased to 44.23~128.0 mS/cm-1, and the preparation process is green and environmentally friendly, the product is degradable, and environmental pollution is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708574A_ABST
    Figure CN119708574A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfonated nano-cellulose film with high proton conductivity and a preparation method thereof, and relates to the field of nano-cellulose films, the method comprises the following steps: taking deionized water as a medium, and under the condition that the pH is 2-3, carrying out light-proof oxidation reaction on cellulose by using sodium periodate to obtain dihydroformylated cellulose; the preparation method comprises the following steps: carrying out Schiff base reductive amination reaction on dihydroformylated cellulose, 2-aminoethanesulfonic acid and 2-methylpyridine borane in deionized water at 59-65 DEG C, and then removing impurities to obtain sulfonated nano cellulose suspension; according to the preparation method, the sulfonated nano-cellulose suspension is molded in a vacuum suction filtration manner, and then is dried to obtain the sulfonated nano-cellulose film with high proton conductivity, so that the problems that cellulose proton conductivity is low, the cellulose is non-degradable and the environment is indirectly polluted by a preparation process are solved, and the proton conductivity is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nanocellulose films, in particular to a sulfonated nanocellulose film with high proton conductivity and a preparation method thereof. Background Art

[0002] In recent years, the stringent requirements for high performance and environmental friendliness of proton exchange membrane fuel cells have led to intensive improvements in proton exchange membrane materials. Currently, the commonly used perfluorosulfonic acid resin membrane (Nafion, Dupont) has poor proton conductivity under low humidity conditions (≤15 mS / cm, 33% RH, basic requirement ≥100 mS / cm), high cost, and non-green material components, which limit its further development. Therefore, there is an urgent need to develop a new type of proton exchange membrane material to address this problem.

[0003] Biomass materials are the best choice for new proton exchange membrane materials. Cellulose, as one of the raw materials for biomass materials, has the advantages of abundant raw materials, rapid regeneration, good environmental and biocompatibility, and biodegradability. However, its surface hydroxyl group has weak deprotonation ability, resulting in its proton conduction efficiency not being able to meet basic requirements, limiting its rapid development in this field.

[0004] Based on the polyhydroxy structure of cellulose, there have been some reports on improving the proton conduction carrier in cellulose membrane by introducing high proton conductivity polymers, strongly deprotonated sulfonic acid groups, phosphoric acid groups, etc. Among them, the introduction of sulfonic acid groups is the most prominent in improving the proton conduction performance, but there are still many problems in the introduction process: First, the source of sulfonic acid groups used, such as acrylic acid, sulfosuccinic acid, etc., has a complex synthesis process, has certain toxicity and will make the synthesized cellulose membrane non-degradable; second, the introduction of sulfonic acid groups through hydrogen bonds or dynamic covalent bonds is prone to cause the loss of acidic groups under long-term use, resulting in poor proton conduction performance. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a sulfonated nanocellulose film with high proton conductivity and a preparation method thereof to solve the problems of low proton conductivity, non-degradability and indirect environmental pollution of cellulose during the preparation process, and has high proton conductivity.

[0006] The present invention is implemented by adopting the following technical solutions: A method for preparing a sulfonated nanocellulose film with high proton conductivity comprises the following steps: S1, using deionized water as the medium, at a pH of 2-3, using sodium periodate to perform a light-protected oxidation reaction on cellulose, the mass ratio of sodium periodate to cellulose being (1.2-1.4): (0.9-1.1), to obtain dialdehyde cellulose; S2, in deionized water at 59-65 °C, dialdehyde cellulose, 2-aminoethanesulfonic acid and 2-methylpyridine borane are subjected to Schiff base reductive amination reaction in a mass ratio of (0.9-1.1): (2.0-6.0): (0.3-0.33), and then impurities are removed to obtain a sulfonated nanocellulose suspension; S3, forming the sulfonated nanocellulose suspension by vacuum filtration, and then drying it to obtain a sulfonated nanocellulose film with high proton conductivity.

[0007] A further improvement of the present invention is: The light-protected oxidation reaction described in S1 was carried out at 48-52 °C for 3.0-3.8 h.

[0008] The cellulose described in S1 is bleached coniferous wood cellulose.

[0009] S1 first disperses the bleached coniferous cellulose uniformly in deionized water, the mass ratio of deionized water to bleached coniferous cellulose is (99~101): (0.9~1.1), then adds sodium periodate to obtain a mixed solution, uses 0.1 M HCl solution to adjust the pH of the mixed solution to 2~3, and finally carries out an oxidation reaction under light-proof conditions to obtain a first reaction solution, and washes the product in the first reaction solution to obtain dialdehyde cellulose.

[0010] S1 uses deionized water and ethanol, combined with vacuum filtration to wash the product until the washing liquid is neutral, to obtain dialdehyde cellulose, and then adds deionized water. The mass ratio of deionized water to bleached coniferous cellulose is (0.9~1.1): (9.9~11.1) to obtain a dialdehyde cellulose suspension.

[0011] S2 adds 2-aminoethanesulfonic acid and 2-methylpyridine borane to the dialdehyded cellulose suspension, and carries out Schiff base reductive amination reaction at 59-65 °C for 10-13 h to obtain a second reaction solution, after which impurities are removed to obtain a sulfonated nanocellulose suspension.

[0012] S2 dialyze the second reaction solution in deionized water for 69-75 hours to obtain a sulfonated nanocellulose suspension. S3 forms the sulfonated nanocellulose suspension on a PVDF membrane by vacuum filtration, and then dries it at 40-50° C. for 5.5-6.5 hours to form a sulfonated nanocellulose film with high proton conductivity on the PVDF membrane. S3 peels off the sulfonated nanocellulose film with high proton conductivity on the PVDF membrane to obtain the sulfonated nanocellulose film with high proton conductivity.

[0013] A sulfonated nanocellulose film with high proton conductivity obtained by the method for preparing a sulfonated nanocellulose film with high proton conductivity as described in any one of the above, wherein the proton conductivity of the sulfonated nanocellulose film is 44.23-128.0 mS / cm -1 .

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a sulfonated nanocellulose film with high proton conductivity. The method comprises the following steps: firstly, in deionized water, at a pH of 2-3, sodium periodate is used to perform a light-proof oxidation reaction on cellulose, and by adjusting the mass ratio of sodium periodate to cellulose, a pair of adjacent hydroxyl groups in the cellulose molecule are oxidized into aldehyde groups to obtain dialdehyde cellulose, and then taurine (2-aminoethanesulfonic acid) containing amino groups and sulfonic acid groups is used in combination with 2-methylpyridine borane as a reducing agent to perform a Schiff base reduction amination reaction on the dialdehyde cellulose, and the sulfonic acid group is smoothly grafted onto the aldehyde group of the dialdehyde cellulose molecular structure through a CN bond, and then impurities are removed to prepare the sulfonated nanocellulose material. The sulfonated modification of cellulose does not change the crystal form of cellulose, and the nano morphology exhibited by the sulfonated nanofibers is calculated by particle size, and the fiber length is 179.37±28.86 nm, and the fiber width is 8.11±3.21 The sulfonated nanocellulose suspension is formed by vacuum filtration, and then dried to obtain a sulfonated nanocellulose film with high proton conductivity. The preparation method of the present invention is green and environmentally friendly, the obtained product is degradable, and compared with the original cellulose, the sulfonated nanocellulose has excellent proton conductivity. After testing, the proton conductivity of the sulfonated nanocellulose film is 44.23~128.0 mS / cm -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 FTIR images of the dialdehyded cellulose, sulfonated nanocellulose and pulp obtained in Examples 1-3 of the present invention.

[0016] Figure 2 The XRD diagrams of the sulfonated nanocellulose and the original pulp obtained in Examples 1-3 of the present invention.

[0017] Figure 3 This is the XPS graph of the sulfonated nanocellulose and the original pulp obtained in Examples 1-3 of the present invention.

[0018] Figure 4 This is the TEM image of the sulfonated nanocellulose obtained in Example 3 of the present invention.

[0019] Figure 5aThis is a graph showing the changes in proton conductivity of the sulfonated nanocellulose and perfluorosulfonic acid resin membranes obtained in Examples 1-3 of the present invention as a function of temperature and humidity.

[0020] Figure 5b This is a graph showing the changes in proton conductivity of the sulfonated nanocellulose and perfluorosulfonic acid resin membranes obtained in Examples 1-3 of the present invention as a function of temperature and humidity.

[0021] Figure 6 It is the formula and specific structural formula for the preparation of sulfonated nanocellulose in the present invention. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0023] The present invention provides a method for preparing a sulfonated micro-nano cellulose film with high proton conductivity, which specifically comprises the following steps, calculated by mass fraction: Step 1, weigh 0.9-1.1 parts of bleached coniferous wood cellulose, measure 99-101 parts of deionized water, add 1.2-1.4 parts of sodium periodate after the cellulose is fully dispersed, use 0.1 M HCl solution to adjust the pH to 2-3, and carry out the bleaching at 48-52 ° C in the dark. Figure 6 The oxidation reaction is performed for 3.0 to 3.8 h, and then washed to neutrality with water and ethanol in combination with vacuum filtration to obtain a dialdehyde cellulose solid with a low water content, the dialdehyde cellulose is denoted as DAC, and 9.9 to 11.1 parts of deionized water are added to obtain a dialdehyde cellulose suspension, that is, a dialdehyde cellulose suspension containing absolutely dry dialdehyde cellulose.

[0024] Step 2, weighing a dialdehyde cellulose suspension containing 0.9-1.1 parts of absolute dry dialdehyde cellulose, 2.0-6.0 parts of 2-aminoethanesulfonic acid, and 0.3-0.33 parts of 2-methylpyridine borane, and performing the following steps at 59-65 °C: Figure 6 The Schiff base reductive amination reaction was performed for 10-13 h, and the suspension of sulfonated nanocellulose was obtained after dialysis in deionized water for 69-75 h. The suspension was then filtered by vacuum on a PVDF membrane (polyvinylidene fluoride membrane) and dried at 40-50 °C for 5.5-6.5 h to construct a sulfonated nanocellulose film, which was recorded as sulfonated nanocellulose (SNC) membrane.

[0025] The internal impedance of the sulfonated nanocellulose film was characterized by electrochemical impedance spectroscopy at a certain temperature and humidity, and the proton conductivity value can be obtained by impedance calculation. The proton conductivity of the sulfonated nanocellulose film was tested to be 44.23~128.0 mS / cm -1 .

[0026] Example 1 The present invention provides a method for preparing a sulfonated nanocellulose film with high proton conductivity, which specifically comprises the following steps: Step 1) Weigh 1 part of bleached coniferous wood cellulose, measure 100 parts of deionized water, add 1.3 parts of sodium periodate after the cellulose is fully dispersed, use 0.1 M HCl solution to adjust the pH to 2, react at 48 ° C in the dark for 3.5 hours, then use water and ethanol, combined with vacuum filtration to assist washing until neutral, add 10 parts of deionized water to obtain a dialdehyde cellulose suspension.

[0027] Step 2) Weigh a dialdehyded cellulose suspension containing 1 part of absolute dry dialdehyded cellulose, 2 parts of 2-aminoethanesulfonic acid, and 0.3 parts of 2-methylpyridine borane, react at 60°C for 12 hours, dialyze in deionized water for 72 hours to obtain a sulfonated nanocellulose suspension, vacuum filter on a PVDF membrane, and then dry at 45°C for 6 hours to obtain a sulfonated nanocellulose film (denoted as SNC-2).

[0028] The proton conductivity of the obtained sulfonated nanocellulose membrane was 61.10 mS / cm at 80 °C and 98% RH. -1 .

[0029] Example 2 The present invention provides a method for preparing a sulfonated nanocellulose film with high proton conductivity, which specifically comprises the following steps: Step 1) Weigh 1 part of bleached coniferous wood cellulose, measure 100 parts of deionized water, add 1.3 parts of sodium periodate after the cellulose is fully dispersed, use 0.1 M HCl solution to adjust the pH to 2, react at 50 ° C in the dark for 3.5 hours, then use water and ethanol, combined with vacuum filtration to assist washing until neutral, add 10 parts of deionized water to obtain a dialdehyde cellulose suspension.

[0030] Step 2) Weigh a dialdehyded cellulose suspension containing 1 part of absolute dry dialdehyded cellulose, 4 parts of 2-aminoethanesulfonic acid, and 0.3 parts of 2-methylpyridine borane, react at 60°C for 12 h, dialyze in deionized water for 72 h to obtain a sulfonated nanocellulose suspension, vacuum filter on a PVDF membrane, and then dry at 40°C for 6.5 h to obtain a sulfonated nanocellulose film (denoted as SNC-4).

[0031] The proton conductivity of the obtained sulfonated nanocellulose membrane was 96.77 mS·cm at 80°C and 98% RH. -1 .

[0032] Example 3 The present invention provides a method for preparing a sulfonated nanocellulose film with high proton conductivity, which specifically comprises the following steps: Step 1) Weigh 1 part of bleached coniferous wood cellulose, measure 100 parts of deionized water, add 1.3 parts of sodium periodate after the cellulose is fully dispersed, use 0.1 M HCl solution to adjust the pH to 2, react at 52 ° C in the dark for 3.5 hours, then use water and ethanol, combined with vacuum filtration to assist washing until neutral, add 10 parts of deionized water to obtain a dialdehyde cellulose suspension.

[0033] Step 2) Weigh a dialdehyded cellulose suspension containing 1 part of absolute dry dialdehyded cellulose, 6 parts of 2-aminoethanesulfonic acid, and 0.3 parts of 2-methylpyridine borane, react at 60°C for 12 h, dialyze in deionized water for 72 h to obtain a sulfonated nanocellulose suspension, vacuum filter on a PVDF membrane, and then dry at 50°C for 5.5 h to obtain a sulfonated nanocellulose film (denoted as SNC-6).

[0034] The proton conductivity of the obtained sulfonated nanocellulose membrane was 128.0 mS·cm at 80 ℃ and 98% RH. -1 The proton conductivity is 44.23 mS·cm at 80℃ and 33% RH. -1 .

[0035] from Figure 1 The FTIR of sulfonated nanocellulose can be used to analyze the changes in the chemical structure characteristics of sulfonated nanocellulose and Pulp. As shown in the figure, the sulfonated nanocellulose has the following characteristics: -1 The characteristic absorption peaks of C=N, S=O, and SO that appeared at the cellulose surface confirmed that the sulfonic acid groups were successfully grafted onto the cellulose molecular structure.

[0036] from Figure 2 The XRD of sulfonated nanocellulose and original cellulose can be used to analyze the changes in the crystal structure. As can be seen from the figure, the cellulose before and after modification shows three main diffraction peaks near 2θ=15°, 17° and 23°, belonging to cellulose type I, indicating that the sulfonation modification of cellulose has not changed the crystal form of cellulose.

[0037] Figure 3 The XPS spectra of sulfonated nanocellulose and original cellulose are shown. It can be seen from the figure that the modified cellulose structure contains nitrogen and sulfur elements, which confirms the successful preparation of sulfonated nanocellulose.

[0038] from Figure 4 TEM shows that the sulfonated nanofibers exhibit a nanomorphology. After particle size calculation, the fiber length is 179.37 ± 28.86 nm and the fiber width is 8.11 ± 3.21 nm.

[0039] from Figure 5a and Figure 5b It can be seen that the proton conductivity changes of the sulfonated nanocellulose films and perfluorosulfonic acid resin membranes obtained in Examples 1-3 of the present invention in 33% RH and 98% RH environments, respectively, and it can be seen that in an environment of 33% RH, the proton conductivity of all sulfonated nanocellulose films is greater than that of the perfluorosulfonic acid resin membrane. The proton conductivity of the sulfonated nanocellulose films and perfluorosulfonic acid resin membranes obtained in Examples 1-3 increases with increasing humidity, and the proton conductivity of the sulfonated nanocellulose film is 128.0 mS / cm at 98% RH and 80°C, showing high proton conductivity performance.

Claims

1. A method for preparing a sulfonated nanocellulose film with high proton conductivity, characterized in that: The following steps are involved: S1, using deionized water as the medium, at a pH of 2-3, using sodium periodate to perform a light-protected oxidation reaction on cellulose, the mass ratio of sodium periodate to cellulose being (1.2-1.4): (0.9-1.1), to obtain dialdehyde cellulose; S2, in deionized water at 59-65 °C, dialdehyde cellulose, 2-aminoethanesulfonic acid and 2-methylpyridine borane are subjected to Schiff base reductive amination reaction in a mass ratio of (0.9-1.1): (2.0-6.0): (0.3-0.33), and then impurities are removed to obtain a sulfonated nanocellulose suspension; S3, forming the sulfonated nanocellulose suspension by vacuum filtration, and then drying it to obtain a sulfonated nanocellulose film with high proton conductivity.

2. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 1, characterized in that: The light-protected oxidation reaction described in S1 was carried out at 48-52 °C for 3.0-3.8 h.

3. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 1, characterized in that: The cellulose described in S1 is bleached coniferous wood cellulose.

4. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 1, characterized in that: S1 first disperses the bleached coniferous cellulose uniformly in deionized water, the mass ratio of deionized water to bleached coniferous cellulose is (99~101): (0.9~1.1), then adds sodium periodate to obtain a mixed solution, uses 0.1 M HCl solution to adjust the pH of the mixed solution to 2~3, and finally carries out an oxidation reaction under light-proof conditions to obtain a first reaction solution, and washes the product in the first reaction solution to obtain dialdehyde cellulose.

5. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 4, characterized in that: S1 uses deionized water and ethanol, combined with vacuum filtration to wash the product until the washing liquid is neutral, to obtain dialdehyde cellulose, and then adds deionized water. The mass ratio of deionized water to bleached coniferous cellulose is (0.9~1.1): (9.9~11.1) to obtain a dialdehyde cellulose suspension.

6. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 5, characterized in that: S2 adds 2-aminoethanesulfonic acid and 2-methylpyridine borane to the dialdehyded cellulose suspension, and carries out Schiff base reductive amination reaction at 59-65 °C for 10-13 h to obtain a second reaction solution, after which impurities are removed to obtain a sulfonated nanocellulose suspension.

7. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 6, characterized in that: S2 dialyze the second reaction solution in deionized water for 69-75 hours to obtain a sulfonated nanocellulose suspension.

8. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 1, characterized in that: S3 forms the sulfonated nanocellulose suspension on a PVDF membrane by vacuum filtration, and then dries it at 40-50° C. for 5.5-6.5 hours to form a sulfonated nanocellulose film with high proton conductivity on the PVDF membrane.

9. The method for preparing a sulfonated nanocellulose film with high proton conductivity according to claim 8, characterized in that: S3 peels off the sulfonated nanocellulose film with high proton conductivity on the PVDF membrane to obtain the sulfonated nanocellulose film with high proton conductivity.

10. A sulfonated nanocellulose film with high proton conductivity obtained by the method for preparing a sulfonated nanocellulose film with high proton conductivity according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of sulfonated cellulose

    CN112142862A

  • Surface-SO3H / - NH2 acid-base pair modified nanosheet modified polymer hybrid proton exchange membrane and preparation thereof

    CN116435563A

  • PH-induced photo-thermal enhanced cellulose hydrogel as well as preparation method and application thereof

    CN116898794A

  • NANO cellulose film used as fuel cell and electrolyte film

    JP2017022044A